Sharp’s Pirate Odyssey, the Spanish Waggoner, and its English Copies: Transmission or appropriation of knowledge? - Montañez Sanabria, Elizabeth (2023)
This article will focus on the cartography resulting from the raids of the English buccaneer Bartholomew Sharp and his pirate comrades in the Spanish American Pacific between 1680 and 1681. Mainly, I will examine some of the atlases produced by William Hack based on the Spanish derrotero of the South Sea that Sharp captured on the coasts of Ecuador. Also, I will examine the copy that the English pirate Basil Ringrose made based on the same waggoner. Our main interest is to determine whether the English cartography resulting from this pirate expedition is a transmission of pirate expertise or an appropriation of Hispanic knowledge.